Formação continuada de professores em serviço : em busca de um currículo em ação intermulticultural - Silva, Regina Helena da (2009)
The research had as a focus the investigation of the group work: the teachers and the coordinator teacher of a primary school cycle I (1st to 4th grade) of the state net of teaching and a university professor, having the formative/collaborative work as an interpretative tool to direct intervene actions with the aim to sensitize/raise awareness of the teachers to issues such as equality, differences and inequality. The theoretical references used are based on post critical theories, which have as their source the Marxist theory, but such theories surpass the class concept, by adding other concepts such as culture, religion, gender, race/ethnicity among others. The data was analyzed through the following theoretical categories: alterity, difference and equality, expectation and identity. The sensitivity process about the issues aimed to contribute with the teachers practices either in the methodology or with the content selection towards an inter/multicultural action. The research proved that is not enough for the school curriculum to change in relation to the inter/multiculturalism only happen in the bureaucratic field, in the paper, but also in the sensitivity/conscience awareness processes for the implementation of new contents aiming this issue. The sensitivity process should happen in all the stages if the formation and this process should be ongoing and permanent.